Low-cost technology for screening uterine cervical cancer - Aditya Parashari; Veena Singh; Ashok Sehgal; Labani Satyanarayana; Pushpa Sodhani; Madan M. Gupta (The World Health Organization, 2000)
We report on an illuminated, low-cost (Rs 1500 (US$ 36)) magnifying device (Magnivisualizer) for detecting precancerous lesions of the uterine cervix. A total of 403 women attending a maternal and child health care clinic who had abnormal vaginal discharge and related symptoms were referred for detailed pelvic examination and visual inspection by means of the device after the application of 5% (v/v) acetic acid. Pap smears were obtained at the same time. The results were compared with those obtained using colposcopy and/or histology. The Magnivisualizer improved the detection rate of early cancerous lesions from 60%, for unaided visual inspection, to 95%. It also permitted detection of 58% of cases of low-grade dysplasia and 83% of cases of high-grade dysplasia; none of these cases were detectable by unaided visual inspection. For low-grade dysplasia the sensitivity of detection by means of the Magnivisualizer was 57.5%, in contrast with 75.3% for cytological examination. However, the two methodologies had similar sensitivities for higher grades of lesions. The specificity of screening with the Magnivisualizer was 94.3%, while that of cytology was 99%. The cost per screening was approximately US$ 0.55 for the Magnivisualizer and US$ 1.10 for cytology.